2020
DOI: 10.1186/s40494-020-00374-3
|View full text |Cite
|
Sign up to set email alerts
|

Study on microbubble of cellulose acetate microfilm of the Republic of China (AD 1912–1949) collected in the Second Historical Archives of China

Abstract: The white spots known as microbubbles that are formed in cellulose acetate film, significantly affects the texture of the image. However, the formation of microbubbles and their corresponding microstructure are poorly understood. In this paper, cellulose acetate microfilm from the Republic of China (AD 1912-1949) collected in the Second Historical Archives of China was chosen as a prototype to investigate the causes of microbubble disease for the first time. A comparative study was conducted between the film s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…More recently, a study of twentieth century Chinese CA microfilm linked deacetylation of the film substrate to the migration of TPP and the formation of microbubbles. The study also found increased hydrophilicity in areas of the film affected by microbubble formation [85]. In other studies, TPP's hydrolysis products of phenol and diphenyl phosphate have been detected, suggesting plasticiser and migration of by-products can also occur [4,86].…”
Section: Factors Affecting Migrationsupporting
confidence: 57%
“…More recently, a study of twentieth century Chinese CA microfilm linked deacetylation of the film substrate to the migration of TPP and the formation of microbubbles. The study also found increased hydrophilicity in areas of the film affected by microbubble formation [85]. In other studies, TPP's hydrolysis products of phenol and diphenyl phosphate have been detected, suggesting plasticiser and migration of by-products can also occur [4,86].…”
Section: Factors Affecting Migrationsupporting
confidence: 57%
“…Plastics in collections are challenging to preserve, as they tend to degrade faster than other materials found in artworks [9][10][11][12][13][14][15][16][17]. Synthetic organic/inorganic pigments also have stability issues [18][19][20][21][22][23][24][25] and their alteration in modern polymeric paints continues to be a subject of ongoing research in art conservation [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have studied the causes of microbubble diseases of cellulose acetate micro lm collected in the Second Historical Archives of China [15]. The results showed that microbubble disease is accompanied by the production of vinegar syndrome.…”
Section: Introductionmentioning
confidence: 99%